2019
DOI: 10.1186/s12920-019-0501-z
|View full text |Cite
|
Sign up to set email alerts
|

Genes CEP55, FOXD3, FOXF2, GNAO1, GRIA4, and KCNA5 as potential diagnostic biomarkers in colorectal cancer

Abstract: Background Colorectal cancer (CRC) is one of the leading causes of death by cancer worldwide and in need of novel potential diagnostic biomarkers for early discovery. Methods We conducted a two-step study. We first employed bioinformatics on data from The Cancer Genome Atlas to obtain potential biomarkers and then experimentally validated some of them on our clinical samples. Our aim was to find a methylation alteration common to all clusters, with the potential of beco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 38 publications
3
48
0
Order By: Relevance
“…CRC is one of the leading causes of cancer deaths worldwide 52 , and FOXF2 predominantly plays an anticancer role in CRC. A study by Hauptman et al showed that the FOXF2 gene was hypermethylated in 81.1% of CRC samples and was downregulated in 98.9% of the samples 26 . In addition, Chen, Zhang et al 27,28 .…”
Section: Colorectal Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…CRC is one of the leading causes of cancer deaths worldwide 52 , and FOXF2 predominantly plays an anticancer role in CRC. A study by Hauptman et al showed that the FOXF2 gene was hypermethylated in 81.1% of CRC samples and was downregulated in 98.9% of the samples 26 . In addition, Chen, Zhang et al 27,28 .…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Therefore, regulating the expression level of FOXF2 is an ideal treatment for tumours. Specifically, decreased FOXF2 expression is a marker of poor prognosis in grade II of TNBC 72 , NSCLC 20 , CRC 26 , ESCC 68 , GC 33 . Inhibitors of miR-200, miR-301, miR-182, miR-130, and miR-519 can be used to treat tumours.…”
Section: Clinical Significance Of Foxf2 In Tumoursmentioning
confidence: 99%
See 1 more Smart Citation
“…Although knockdown of GRIA4 has been associated with dysregulation of genes involved in invasion and metastasis [15], its functional role in cancer is not fully elucidated. Interestingly, GRIA4-associated CGI has been found hypermethylated in CRC and adenomas [3,4,16].…”
Section: Introductionmentioning
confidence: 99%
“…Related clinical studies have shown that CEP55 can be used as a diagnostic and prognostic marker for several cancers. For example, Nina Hauptman et al [13] found that CEP55 is a potential biomarker for colorectal cancer through bioinformatics methods and clinical studies; Yang Jia et al [14] found that in esophageal squamous cell carcinoma (ESCC), CEP55 overexpression is associated with poor prognosis in patients with locally advanced ESCC. Overexpression of CEP55 was significantly associated with a reduction in overall survival after surgery.…”
Section: Introductionmentioning
confidence: 99%